Generation of Full-Length Class I Human Leukocyte Antigen Gene Consensus Sequences for Novel Allele Characterization. (6th January 2020) - Clark, Peter M; Duke, Jamie L; Ferriola, Deborah; Bravo-Egana, Valia; Vago, Tunde; Hassan, Aniqa; Papazoglou, Anna; Monos, Dimitri
Abstract: BACKGROUND: Routine, high-resolution human leukocyte antigen (HLA) genotyping by next generation sequencing within clinical immunogenetics laboratories can now provide the full-length gene sequence characterization of fully phased HLA alleles. This powerful technique provides insights into HLA variation beyond the traditionally characterized antigen recognition domain, providing sequence annotation across the entire gene including untranslated and intronic regions and may be used to characterize novel alleles from massively parallel sequencing runs. METHODS: We evaluated the utility of the Omixon Holotype HLA assay to generate credible, fully phased full-length gene consensus sequences for 50 individuals at major histocompatibility complex, class I, A ( HLA-A ), HLA-B, and HLA-C loci (300 genotyped alleles in total) to identify and characterize novel class I HLA alleles using our downstream analytical pipeline. RESULTS: Our analysis revealed that 7.7% (23/300) of genotyped class I HLA alleles contain novel polymorphisms. Interestingly, all of the novel alleles identified by our analysis were found to harbor sequence variations within intronic regions of the respective locus. In total our analysis identified 17 unique novel class I HLA alleles from 23 of the 300 genotyped alleles and generated full-length gene sequence annotations for 9 previously incompletely annotated HLA class I allele sequences derived from 14 of the 300 genotyped alleles. CONCLUSIONS: The demonstrated utility of the Omixon Holotype HLA assay in combination with our downstream analytical framework to generate fully phased, full-length gene consensus sequences for the identification and characterization of novel HLA alleles, facilitates the study of HLA polymorphism beyond the antigen recognition domain in human health and disease.